TARGETING SELECTIVE TUMOURS BY DEPLOYING MAGNANO PARTICLES THROUGH NANJECTS: RECENT DRUG DELIVERY : Pharmaceutical Science-Drug Delivery - PRIYANKA G; RAJAJEYAKUMAR M (International Journal of Life Science and Pharma Research, 2019)
About 1.2 million new cancer cases have been diagnosed in 1998 worldwide and 2.5 million cases have been recorded in 2009 in India alone. Cancer is thus a major leading public problem that always remains first cause of death in both developed and developing countries (K.U. Devi 2009). Various promising treatment modalities for cancer starts from surgery or tumour removal, radiation, chemotherapy, immunotherapy, targeted therapy, employing hormones till stem cell transplantation procedures. Still, cancer is not completely eradicated from the body. One of the prime cons of these therapies is they over act during the treatment process. It damages the homeostatic balance of leading to increase in mortality rates widely across the world. Beyond the management of cancer the worse phase is pain experienced during the treatment of cancer. Such unrelieved pain has impact on their sleep, daily activities, food intake and at times their chronic pain leads them to commit suicide. Thus researchers have recently engineered a neo technique by impregnating Magnano particles into micro needles less than a hair follicle diameter to counteract tumour cells. Healthy cells will not be facing the damage amidst the targeted drug delivery to the cancerous cells. These non-toxic Magnano vehicles can overcome the debilitating systemic toxicities caused by cytotoxic chemotherapies. Moreover nano fine particles opt the Trojan horse mechanism to initiate tumour death. Its advanced property of possessing extensive surface-to-volume ratio is projected in its functionality through surface chemistries, especially when these nanoparticles are received in combinatorial with micro magnets. Thus Nanjects not only avoid side effects caused during cancer therapies but is also applicable for vaccine delivery which can eventually overcome fear and stress in Trypanophobia individuals.